Ekonomi Politik Kebijakan Penyiaran Indonesia: Aspirasi, Pilihan dan Realitas - Wahyuni, Hermin Indah (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2006)
The creation f new broadcasting laws in Indonesia was hindered by tensions between reformist groups bent on fundamental changes to the broadcasting system and conservative group which wanted to continue the status quo. In comparison to the previous broadcasting regulations under the Suharto regime, the new broadcasting law is aimed to changing the television broadcasting system in Indonesia so that it would be more democratic in ideas, institution and policies. The article argues that efforts were made to implement some of the ideals of democratic broadcasting system, but in practice these were weakly supported and their future in uncertain. Fundamental change in the new broadcasting system are still unclear. A new democratic political leadership does not control there regulation and restructuring of the new Indonesia broadcasting system. Rather, the some bureaucrats have reorganised themselves into new constellations.